Enhancing performance of ZnO/NiO UV photodetector by piezo-phototronic effect. Issue 54 (16th May 2016) - Yin, Bing; Qiu, Yu; Zhang, Heqiu; Chang, Yue; Yang, Dechao; Hu, Lizhong
Abstract : The performance of the ZnO/NiO UV photodetector is enhanced by piezo-phototronic effect. Abstract : In this work, a UV photodetector based on a ZnO/NiO core/shell nanorods array is fabricated by hydrothermal growth processes and thermal oxidation. Compressive strain is applied to enhance the I light and sensitivity of the UV photodetectors. Under a 1 N compressive strain at −3.5 V, the enhancement in I light and sensitivity of the UV photodetector is about 74% and 78.7%, respectively. The possible working principle is that the negative piezo-polarization at the ZnO/NiO interface shifts the depletion region to the ZnO side leading to an increase of the photon-absorption volume. This work may provide a potential approach to enhance the performance of the ZnO/NiO UV photodetector.